Experimental study of hybrid crack of coal-measure rocks with image and acoustic emission monitoring using SCB method - Baoyan Zhi; Zitao Yao; Guanchao Ma; Shichang Liang; Binchang Wang (Energy Exploration & Exploitation)
Most instability damage in rock engineering results from the accumulation of microcracks. Fracture tests were conducted in I/II mixed mode using semi-circular bending (SCB) Specimens comprising coal, sandy mudstone, and sandstone with five different pre-fracture angles ( β ). The evolution of fracture processes and micro-deformation field in rocks were analyzed using digital image calculation method (DICM) and acoustic emission (AE) monitoring. The findings indicate that as β increases, K I gradually decreases, while K II initially increases and then decreases with β growth. Integrating load force-time curves with AE signals reveals three stages in the fracture processes of coal, sandy mudstone, and sandstone: crack initiation, stable crack expansion, and destabilization damage. Furthermore, a comprehensive comparison confirms that experimental results of fracture toughness ( K eff ) for the three rock specimens in I/II hybrid crack mode are consistent with the principles of the modified maximum circumferential stress (MMTS) theory.